The Impact of Violence, Bullying and Intolerance on Early Childhood - Maromi, Choirul; Turhan Yani, Muhammad; SyaÔÇÖdullah, Achmad; Jannah, Miftakhul; Yes Matheos Lasarus Malaikosa, Yes (Journal of Islamic Education Students (JIES), 2024)
This research aims to analyze the impact of violence, bullying and intolerance on young children at the Al-Ikhsan Islamic Kindergarten. The research method used is a combination of qualitative and quantitative. The qualitative approach involves in-depth interviews with teachers, parents, and students to gain in-depth perspectives on their experiences and perceptions regarding violence, bullying, and intolerance. Meanwhile, the quantitative approach uses questionnaires distributed to all students and parents to measure the frequency, type and impact of these events. The research results show that violence, bullying and intolerance have a significant impact on children's emotional and social development. Children who experience violence and bullying tend to show symptoms of stress, anxiety and decreased academic performance. In addition, intolerance in the school environment can hinder the development of tolerance and cooperation among children. This research emphasizes the importance of early intervention and educational programs that focus on developing social and emotional skills to create safe and inclusive learning environments.